Controllable preparation method and application of nano cage type thiourea-resorcinol-formaldehyde resin adsorbent
By synchronously doping thiourea and silica during the growth of the phenolic resin layer, nanocage resin microspheres were prepared, which solved the problems of low adsorption capacity and slow adsorption rate of existing gold adsorbents, and efficient selective adsorption of gold ions was achieved.
Patent Information
- Application Number
- CN202510056767.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The low adsorption capacity, slow adsorption rate and low site recognition of existing gold adsorbents limit their application in gold recycling.
By using nanocage thiourea-resorcinol-formaldehyde resin adsorbent, the nanocage nanospheres are used as hard templates to synchronize the thiourea and silica during the growth of the phenolic resin layer, and finally the silica template is removed to prepare nanocage resin microspheres for efficient capture of gold in electronic waste solution.
Large capacity and excellent selective adsorption of gold ions are achieved, which significantly improves the efficiency and selectivity of gold recovery.
Smart Images

Figure CN119746818A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of adsorption and separation functional materials, and relates to the controllable preparation of a nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent and its application in selectively separating gold. Background Art
[0002] As a global strategic resource, gold is not only of great significance in national defense and economic security, but its excellent physical and chemical properties also make it widely used in jewelry, currency, electronic equipment, chemical catalysis and other fields. However, the high demand for gold from industry and society has triggered tremendous pressure for its mining and recycling. Especially in the context of the rapid renewal of electronic products, a large amount of electronic waste is generated, in which the gold content in the leachate is as high as 1-2000ppm, which is much higher than the 1-30ppm in natural ore. This provides important environmental significance and considerable economic potential for the extraction of gold from electronic waste. Nevertheless, the recovery process of gold is extremely complicated due to competition with multiple metals (such as palladium, copper, silver, chromium, aluminum and cobalt). This situation highlights the need to develop highly selective and efficient gold recovery technologies.
[0003] The adsorption method is regarded as one of the key methods for recovering trace gold due to its low cost, high safety and strong environmental protection. In addition, the method is simple to operate and suitable for continuous processing, which further improves its practicality. The core of adsorption technology lies in the performance of the adsorbent material, which directly determines the recovery efficiency. However, common adsorbents currently have problems such as low adsorption efficiency and poor regeneration performance, which limits their practical application range. Therefore, it is particularly important to develop new adsorbent materials with high adsorption capacity.
[0004] Among many materials, phenolic resin is considered to be a promising gold adsorption material due to its advantages such as controllable synthesis conditions, environmental friendliness, strong chemical stability, low cost and easy industrial production. Although phenolic resin has excellent adsorption capacity in theory, its traditional synthesis methods, such as the classical solvothermal method, usually require harsh reaction conditions, and the obtained materials have great limitations in morphology and size control. To overcome these problems, we based on the extended Based on phenol-formaldehyde resin, the morphology and adsorption performance of the material were studied in depth by combining hard template method and heteroatom doping technology. This improvement strategy helps to improve the adsorption capacity and selectivity of phenolic resin, making it show greater potential in the adsorption and separation application of gold. Summary of the invention
[0005] In order to solve the problems of low adsorption capacity, slow adsorption rate and low site recognition of gold adsorbents in the prior art, the present invention provides a controllable preparation of a nano cage type thiourea-resorcinol-formaldehyde resin adsorbent and its application in selectively separating gold. Using silicon dioxide nanospheres as hard templates, thiourea and silicon dioxide are doped synchronously during the growth of the phenolic resin layer, and finally the silicon dioxide template is etched away to controllably prepare cross-shrinkage resin nanocage microspheres and apply them to efficiently capture gold in electronic waste dissolution.
[0006] In order to achieve the above technical purpose, the technical solution adopted by the present invention is as follows:
[0007] A controllable preparation method of a nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent comprises the following steps:
[0008] (1)SiO 2 Preparation of microspheres
[0009] First, a certain amount of ethanol, deionized water and ammonia water were mixed in a flask, and then a certain amount (V 1 )TEOS, in T 1 Next reaction time t 1 ; Then add quantitative (V 2 )TEOS, continue in T 1 Next reaction time t 2 The precipitated product was collected by centrifugation, washed several times with distilled water and ethanol respectively, and finally, the powder was dried in vacuum.
[0010] (2)SiO 2 @TRF nanosphere preparation
[0011] The silica nanospheres produced in step (1) are placed in a round-bottom flask, and an appropriate amount of distilled water is added. Ultrasound is performed to completely disperse the nanospheres. A certain amount of ammonia water, resorcinol and thiourea are added under stirring. Stir for a period of time t 3 After that, add quantitative formaldehyde and silane coupling agent, 2 Stir the reaction for a period of time t 4 The product was collected by centrifugation, washed several times with distilled water and ethanol respectively, and finally, the powder was vacuum dried to obtain SiO 2 @TRF;
[0012] (3) Preparation of TRF nanospheres
[0013] Take the SiO obtained in step (2) 2 @TRF is placed in a centrifuge tube, a certain concentration of hydrofluoric acid aqueous solution is added, and it is placed on a shaker for etching for a period of time t 5; The product was collected by centrifugation, washed several times with distilled water and ethanol respectively, and finally, the powder was vacuum dried.
[0014] Preferably, in step (1), the ratio of ethanol, water, ammonia and silane coupling agent is 30 mL: 5 mL: 2 mL: 5.2 mL, V 1 and V 2 The volume ratio is 0.2:5, T 1 is 25-30℃, reaction time t 1 The reaction time is 20-30min. 2 For 12 hours.
[0015] Preferably, in step (2), the amount ratio of the silica nanospheres, resorcinol, formaldehyde, thiourea, ammonia water, silane coupling agent and deionized water is 200 mg: 0.00182 mol: 0.00373 mol: 0.00342 mol: 150 μl: 100 μl: 25-30 mL; T 2 At 30°C, the reaction time t 3 The reaction time is 20min. 4 It is 24 hours.
[0016] In step (2), the type of the silane coupling agent is tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), or tetrapropoxysilane (TPOS). According to the use of different silane coupling agents, the material is named TRF-(silane coupling agent).
[0017] Preferably, in step (3), the SiO 2 @The dosage ratio of TRF and hydrofluoric acid aqueous solution is 50 mg:5 mL, the concentration of hydrofluoric acid is 1% wt, and the reaction time is t 5 0.5-3h.
[0018] The nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent prepared by the invention can be controlled to be used for the selective adsorption and separation of gold ions in a solution.
[0019] The beneficial effects of the present invention are:
[0020] The present invention makes use of the strong affinity between nitrogen, sulfur and noble metal ions, adopts relatively mild synthesis conditions, and regulates the microstructure of the material through a template method to prepare nitrogen and sulfur co-doped phenolic resin nanomaterials, thereby achieving large capacity and excellent selective adsorption of gold ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Scanning electron microscope images of TRF materials prepared using different silane coupling agents.
[0022] Figure 2 The effect of different silane coupling agents and etching on the adsorption capacity of gold ions by TRF.
[0023] Figure 3 The SiO prepared in Example 1 2 @Infrared spectra of TRF and TRF-TEOS materials.
[0024] Figure 4 The figure shows the effect of pH value on the adsorption capacity of gold ions by the TRF-TEOS adsorbent prepared in Example 1.
[0025] Figure 5 The adsorption kinetics of gold ions by the TRF-TEOS adsorbent prepared in Example 1 and its model fitting curve.
[0026] Figure 6 The effect of temperature on the adsorption equilibrium of gold ions by the TRF-TEOS adsorbent prepared in Example 1 and its model fitting curve.
[0027] Figure 7 It is the adsorption selectivity of the TRF-TEOS adsorbent prepared in Example 1.
[0028] Figure 8 This is the adsorption regeneration performance of the TRF-TEOS adsorbent prepared in Example 1. DETAILED DESCRIPTION
[0029] In the specific implementation of the present invention, the recognition performance evaluation is carried out according to the following method: the static adsorption experiment is used to complete. The adsorption capacity of 1.0 mg of TRF-TEOS for gold ions is tested in the pH range of 1.0-8.0, and the content of gold ions after adsorption is measured by inductively coupled plasma emission spectrometer, and the optimal adsorption pH is determined according to the results; secondly, the effect of adsorption time on the adsorption capacity of TRF-TEOS is studied, and the data are fitted, calculated and analyzed using Pseudo first-order model, Pseudo second-order model, etc.; to study the maximum adsorption capacity of TRF-TEOS, we conducted an adsorption equilibrium test in the range of 500-1000 ppm of gold ion concentration, and fitted the adsorption data using Langmuir model and Freundlich model, and calculated the adsorption capacity according to the results; and a printed circuit board is selected as an actual sample to study the selective adsorption performance of TRF-TEOS; finally, its adsorption regeneration performance is tested.
[0030] The present invention will be further described below in conjunction with specific implementation examples.
[0031] Embodiment 1:
[0032] Preparation of TRF-TEOS:
[0033] (1) 400nm SiO 2 Preparation of microspheres
[0034] First, 30 mL of ethanol, 5 mL of deionized water, and 2 mL of ammonia water were mixed in a 100 mL flask, and then 0.2 mL of TEOS was added under stirring (600 rpm) and reacted at 30°C for 30 min. Then 5 mL of TEOS was added and the reaction continued at 30°C for 12 h. The precipitated product was collected by centrifugation and washed twice with distilled water and ethanol respectively. Finally, the powder was vacuum dried at 60°C for 24 h.
[0035] (2)SiO 2 @TRF nanosphere preparation
[0036] Take 200 mg of the product in step (1) and place it in a 100 ml round-bottom flask, add 25 ml of distilled water, and disperse it completely by ultrasound. Then, under stirring (600 rpm), add 150 μl of ammonia water, 200 mg of resorcinol, and 260 mg of thiourea. After stirring for 20 minutes, add 280 μl of formaldehyde and 100 μl of TEOS, and stir and react at 30°C for 24 hours. Collect the product by centrifugation, wash it twice with distilled water and ethanol respectively, and finally, dry the powder in vacuum at 60°C for 24 hours.
[0037] (3) Preparation of TRF-TEOS nanospheres
[0038] Take the SiO obtained in step (2) 2 @TRF 50mg was placed in a centrifuge tube, 5ml of 1% hydrofluoric acid aqueous solution was added, and the tube was placed on a shaker for 1h. The product was collected by centrifugation, washed twice with distilled water and ethanol respectively, and finally, the powder was vacuum dried at 60℃ for 24h.
[0039] Figure 1 It shows that the microstructure of the material can be regulated by different silane coupling agents;
[0040] Figure 2 It shows that among TRF-TMOS, TRF-TEOS and TRF-TPOS, TRF-TEOS has better adsorption performance;
[0041] Figure 3 It is shown that the characteristic peak of NC=S bond appears, indicating the successful doping of thiourea;
[0042] Embodiment 2:
[0043] Preparation of TRF-TPOS:
[0044] (1) 400nm SiO 2 Preparation of microspheres
[0045] First, 30 ml of ethanol, 5 ml of deionized water and 2 ml of ammonia water were mixed in a 100 ml flask, and then 0.2 ml of TEOS was added under stirring (600 rpm) and reacted at 30°C for 30 min. Then 5 ml of TEOS was added and the reaction continued at 25°C for 12 h. The precipitated product was collected by centrifugation and washed twice with distilled water and ethanol respectively. Finally, the powder was vacuum dried at 60°C for 24 h.
[0046] (2)SiO 2 @TRF nanosphere preparation
[0047] Take 200 mg of the product in step (1) and place it in a 100 ml round-bottom flask, add 25 ml of distilled water, and disperse it completely by ultrasound. Then, under stirring (600 rpm), add 150 μl of ammonia water, 200 mg (0.00182 mol) of resorcinol, and 260 mg (0.00342 mol) of thiourea. After stirring for 20 minutes, add 280 μl (0.00373 mol) of formaldehyde and 100 μl of TPOS, and stir and react at 30°C for 24 hours. Collect the product by centrifugation, wash it twice with distilled water and ethanol respectively, and finally, dry the powder in vacuum at 60°C for 24 hours.
[0048] (3) Preparation of TRF-TPOS nanospheres
[0049] Take the SiO obtained in step (2) 2 @TRF 50mg was placed in a centrifuge tube, 5ml of 1% hydrofluoric acid aqueous solution was added, and the tube was placed on a shaker for 1h. The product was collected by centrifugation, washed twice with distilled water and ethanol respectively, and finally, the powder was vacuum dried at 60℃ for 24h.
[0050] Example 3
[0051] Preparation of TRF-TMOS:
[0052] (1) 400nm SiO 2 Preparation of microspheres
[0053] First, 30 ml of ethanol, 5 ml of deionized water and 2 ml of ammonia water were mixed in a 100 ml flask, and then 0.2 ml of TEOS was added under stirring (600 rpm) and reacted at 30°C for 30 min. Then 5 ml of TEOS was added and the reaction continued at 25°C for 12 h. The precipitated product was collected by centrifugation and washed twice with distilled water and ethanol respectively. Finally, the powder was vacuum dried at 60°C for 24 h.
[0054] (2)SiO 2 @TRF nanosphere preparation
[0055] Take 200 mg of the product in step (1) and place it in a 100 ml round-bottom flask, add 25 ml of distilled water, and disperse it completely by ultrasound. Then, under stirring (600 rpm), add 150 μl of ammonia water, 200 mg (0.00182 mol) of resorcinol, and 260 mg (0.00342 mol) of thiourea. After stirring for 20 minutes, add 280 μl (0.00373 mol) of formaldehyde and 100 μl of TMOS, and stir and react at 30°C for 24 hours. Collect the product by centrifugation, wash it twice with distilled water and ethanol respectively, and finally, dry the powder in vacuum at 60°C for 24 hours.
[0056] (3) Preparation of TRF-TPOS nanospheres
[0057] Take the SiO obtained in step (2) 2 @TRF 50mg was placed in a centrifuge tube, 5ml of 1% hydrofluoric acid aqueous solution was added, and the tube was placed on a shaker for 1h. The product was collected by centrifugation, washed twice with distilled water and ethanol respectively, and finally, the powder was vacuum dried at 60℃ for 24h.
[0058] Test Example 1:
[0059] Accurately weigh 8 portions of 1 mg of TRF-TEOS prepared under the conditions described in Example 1, add them to 3 mL of gold ion solution with a pH value of 1, 2, 3, 4, 5, and 6 and a concentration of 1000 mg / L, place them on a shaker at 25°C for adsorption for 12 hours, and collect the supernatant. The remaining gold ion concentration in the solution is detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments are performed.
[0060] Figure 4 It shows that TRF-TEOS achieves the optimal adsorption effect at pH 5.
[0061] Test Example 2:
[0062] Accurately weigh 10 portions of 1 mg TRF-TEOS, add them to 3 mL of a gold ion solution with a concentration of 1000 mg / L and a pH of 6, place them on a shaker at 25°C and adsorb for 5, 10, 15, 30, 60, 90, 120, 240, 480, and 720 min, and collect the supernatant. The remaining gold ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed.
[0063] Figure 5It shows that the adsorption of gold by TRF-TEOS conforms to the pseudo-first-order kinetic model, indicating that the adsorption process is mainly controlled by the dominant role of chemical adsorption.
[0064] Test Example 3:
[0065] Accurately weigh 6 portions of 1 mg of TRF-TEOS and add them to 5 mL of gold ion solution (pH 5) with concentrations of 400, 500, 600, 700, 800, and 900 mg / L, respectively. Place them on a shaker at 25°C for 12 hours to adsorb and collect the supernatant; place them on a shaker at 35°C for 12 hours to adsorb and collect the supernatant; place them on a shaker at 45°C for 12 hours to adsorb and collect the supernatant. The remaining gold ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed.
[0066] Figure 6 It was shown that the adsorption capacity of TRF-TEOS increased significantly with increasing temperature, indicating that the adsorption process had endothermic characteristics.
[0067] Test example 4:
[0068] Accurately weigh 3 mg of TRF-TEOS prepared under the conditions described in Example 1, add 5 mL of an actual test sample (pH = 3) containing Au (III), Pd (II), Al (III), Co (II), Cr (III), Cu (II), Na (I), Ni (II), Zn (II), etc. leached from 10 g of waste circuit boards using aqua regia, place on a shaker at 25°C for adsorption for 12 h, collect the supernatant, and use an inductively coupled plasma emission spectrometer (ICP) to detect the residual concentration of various ions in the solution. Perform two parallel experiments.
[0069] Figure 7 It shows that TRF-TEOS achieved a gold recovery rate of 83.8%, which significantly exceeded the adsorption performance of other ions in the solution and had excellent selectivity for gold ions.
[0070] Test Example 5:
[0071] Accurately weigh 10 mg of TRF-TEOS, add 10 mL of a gold ion solution with a concentration of 300 mg / L and a pH value of 5, and place it on a shaker at 25°C for adsorption for 12 hours. After taking the supernatant, remove the solution, wash with deionized water, add 10 mL of an eluent prepared with 1 mol / L thiourea and 0.1 mol / L hydrochloric acid, continue to place it on a shaker for desorption for 1.5 hours, then collect the adsorbent by centrifugation, remove the solution, wash with deionized water and dry. This is one set of cycles, and a total of six cycles were performed. The remaining gold ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed.
[0072] Figure 8 The absorption efficiency still remained at 93.8% after five absorption–desorption cycles, demonstrating the excellent durability and reusability of TRF-TEOS.
[0073] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A controllable preparation method of a nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent, characterized in that: The steps include: (1) Preparation of SiO2 microspheres First, a certain amount of ethanol, deionized water and ammonia water are mixed in a flask, and then a volume of TEOS of V1 is added under stirring at a certain speed r, and the reaction is carried out at a reaction temperature T1 for a period of time t1; then a volume of TEOS of V2 is added, and the reaction is continued at T1 for a period of time t2, and the precipitated product is collected by centrifugation, and washed with distilled water and ethanol for several times respectively, and finally, the powder is vacuum dried; (2) Preparation of SiO2@TRF nanospheres The silica nanospheres produced in step (1) are placed in a round-bottom flask, an appropriate amount of distilled water is added, and the nanospheres are completely dispersed by ultrasound. A certain amount of ammonia water, resorcinol and thiourea are added under stirring; after stirring for a period of time t3, a certain amount of formaldehyde and a silane coupling agent are added, and the reaction is stirred at T2 for a period of time t4; the product is collected by centrifugation, and washed with distilled water and ethanol for several times respectively, and finally, the powder is vacuum dried to obtain SiO2@TRF; (3) Preparation of TRF nanospheres The SiO2@TRF obtained in step (2) is placed in a centrifuge tube, a certain concentration of hydrofluoric acid aqueous solution is added, and the tube is placed on a shaker for etching for a period of time t5; the product is collected by centrifugation, and washed several times with distilled water and ethanol respectively, and finally, the powder is vacuum dried.
2. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (1), the usage ratio of ethanol, water, ammonia water and silane coupling agent is 30 mL: 5 mL: 2 mL: 5.2 mL, and the volume ratio of V1 to V2 is 0.2:
5.
3. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (1), T1 is 25-30°C, reaction time t1 is 20-30min, and reaction time t2 is 12h.
4. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (2), the dosage ratio of the silica nanospheres, resorcinol, formaldehyde, thiourea, ammonia water, silane coupling agent and deionized water is 200 mg: 0.00182 mol: 0.00373 mol: 0.00342 mol: 150 μl: 100 μl: 25-30 mL.
5. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (2), T2 is 30° C., reaction time t3 is 20 min, and reaction time t4 is 24 h.
6. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (2), the type of the silane coupling agent is tetramethoxysilane TMOS, tetraethoxysilane TEOS, or tetrapropoxysilane TPOS.
7. The controllable preparation method of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent according to claim 1, characterized in that: In step (3), the dosage ratio of SiO2@TRF and hydrofluoric acid aqueous solution is 50 mg:5 mL, wherein the concentration of hydrofluoric acid is 1% wt, and the reaction time t5 is 0.5-3 h.
8. Use of the nano cage-type thiourea-resorcinol-formaldehyde resin adsorbent prepared by the preparation method according to any one of claims 1 to 7 for selective adsorption and separation of gold ions in a solution.
Citation Information
Patent Citations
Preparation method of dendritic fibrous hollow nitrogen-doped carbon nanocage for supercapacitor
CN111508726A
Preparation method and application method of phenolic resin with hollow shell structure
CN112062919A
Preparation method and application of magnetic light nano-microsphere rapid high-selectivity gold extraction adsorbent
CN117772158A
Preparation method of heteroatom-doped phenolic resin nano adsorbent and application of heteroatom-doped phenolic resin nano adsorbent in selective separation of palladium
CN118515830A
Mesoporous silica supporting gold ion adsorbing compound, and gold ion sensor and gold recovery method using the mesoporous silica
JP2012218991A
Cited By
Cationic cavity-dynamic covalent nano-network function collaborative micro-ring and preparation method and application thereof
CN122229748A